2020
DOI: 10.5009/gnl19266
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Current Traction Techniques for Endoscopic Submucosal Dissection

Abstract: This systematic review aimed to assess the efficacy of the current approach to tissue traction during the endoscopic submucosal dissection (ESD) of superficial esophageal cancer, early gastric cancer, and colorectal neoplasms. We performed a systematic electronic literature search of articles published in PubMed and selected comparative studies to investigate the treatment outcomes of tractionassisted versus conventional ESD. Using the keywords, we retrieved 381 articles, including five eligible articles on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 52 publications
0
79
0
Order By: Relevance
“…A major step would be to drastically change the physical structure of the endoscope which has not changed despite the emergence of newer endoscopic procedures which are considerably different from diagnostic upper endoscopies and colonoscopies, for which the endoscope was originally designed. In addition, modifications to the endoscope and endoscopic accessories such as multibending endoscopes, traction devices, and the recently available double balloon endoluminal interventional platform could also improve the efficiency of these rather long procedures and help decrease the risk of potential injury associated with them 20 21 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A major step would be to drastically change the physical structure of the endoscope which has not changed despite the emergence of newer endoscopic procedures which are considerably different from diagnostic upper endoscopies and colonoscopies, for which the endoscope was originally designed. In addition, modifications to the endoscope and endoscopic accessories such as multibending endoscopes, traction devices, and the recently available double balloon endoluminal interventional platform could also improve the efficiency of these rather long procedures and help decrease the risk of potential injury associated with them 20 21 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, retroflexion requires a slim endoscope with a small working channel that restricts the kind of devices that can be introduced. A traction device such as the clip-and-line method has been reported to overcome these difficulties 3 . However, traction cannot facilitate opening the submucosal layer in the duodenum, because it cannot compress the pyloric sphincter but just pulls the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…nique (S-O clip method, ring-shaped thread countertraction method, clip and thread method). All studies showed comparable success rates but with significant shortening of the procedure time compared with the standard ESD technique [4]. Nomura et al described a single-clip traction method in combination with the pocket creation method without using a line [5].…”
mentioning
confidence: 99%